Concentrations of available heavy metals in mediterranean agricultural soils and their relation with some soil selected properties: a case study in typical mediterranean soils - Nunes, Jose Rato (2018)
The characterization of the content of trace metals in soils is an instrument in many programs of environmental protection, including the establishment of regional-level standards to detect sites affected by contamination. The objectives of the present study were to study the available levels of Cd, Cr, Cu, Ni, Pb, and Zn in surface horizons of agricultural soils in a typical European Mediterranean region, to establish the geochemical baseline concentration (GBC), background level (BL), and reference value (RV) of each of these available metals, and to investigate their possible correlations with soil properties. To establish the GBC and RV values, we used the " standard threshold method". Topsoil samples (0-20 cm) were collected from 630 sites, and extracted with Diethylene Triamine Pentaacetic Acid (DTPA) to determine their available heavy metal concentrations. The GBC values established were: 0.04 to 0.90 mg kg(-1), 0.70 to 2.50 mg kg(-1), 0.10 to 6.30 mg kg(-1), 0.30 to 7.90 mg kg(-1), 0.29 to 4.50 mg kg(-1), and 0.18 to 2.50 mg kg(-1) for Cd, Cr, Cu, Ni, Pb, and Zn, respectively. Soil properties were found to be correlated with the available heavy metal content, suggesting that the enhanced mobility of heavy metals are related to anthropic activities.